Development of a novel intelligent social game design learning platform - ‘Gamewiz’ - Anthony, Nitya (2015)
This project involves the research, design, development and evaluation of a novel intelligent social game design learning platform, that has been named ‘Gamewiz’. This platform enables users to create, share and play games created with an NTU developed Game Editor on the web. ‘Gamewiz’ is targeted at primary school students and leverages game design to teach computational thinking and design thinking via social learning. The novel intelligent ‘Gamewiz’ platform was designed with a 3-tier architecture and developed utilising HTML, Less, CSS, JavaScript, jQuery, PHP, MySQL, AJAX and Apache. ‘Gamewiz’ places an emphasis on the core principles of human computer interaction. ‘Gamewiz’ was further enhanced with the incorporation of Sentiment Analysis via the phpInsight tool to provide effective visual feedback to children on their game creations based on comments by other users. Rules derived from Association Rule Mining via the Weka Data Mining software, were implemented on the site. The order of games displayed to a user changed based on his profile as per the rules implemented. The design of ‘Gamewiz’ was based on user research which involved the Unity Game Engine and the Game Editor to create games and log data. The design process for ‘Gamewiz’ involved further research via field studies, interviews, surveys and competitive analysis to create a user-centric learning platform. User data collection and testing of the Game Editor was conducted through various workshops in addition to a field study at a coding camp in Singapore. Survey, interview and field study findings of students had revealed the strong desire for a social element to the Game Editor.‘Gamewiz’, the novel intelligent social game learning platform makes learning computational thinking through game design more attractive and beneficial for children and is a pioneer in this nascent field with immense interest indicated for its commercial deployment by education service providers in Singapore.